Remarkable anticancer activity of Teucrium polium on hepatocellular carcinogenic rats - Movahedi, Ariyo; Basir, Rusliza; Rahmat, Asmah; Charaffedine, Mohammad; Othman, Fauziah (Hindawi Publishing Corporation, 2014)
The term cancer has been concomitant with despair, agony, and dreadful death. Like many other diseases, herbal therapy has been used to prevent or suppress cancer. The present study investigated the capability of the decoction of Teucrium polium L. from Lamiaceae family to protect liver cells against hepatocellular carcinoma in carcinogenesis-induced animal model. After 28 weeks of treatment with decoction of Teucrium polium L., serum biochemical markers including ALT, AST, AFP, GGT, ALP, HCY, TNF-α, α2MG, and CBG have been regulated auspiciously. Total antioxidant status also has been increased intensely. Liver lesion score in treated group was lessened and glucocorticoid activity has been intensified significantly. In conclusion, Teucrium polium L. decoction might inhibit or suppress liver cancer development.